No observed effect of homologous recombination on influenza C virus evolution. - Han, G; Boni, M; Li, S (2010)
The occurrence of homologous recombination in influenza viruses has been under some debate recently. To determine the extent of homologous recombination in influenza C virus, recombination analyses of all available gene sequences of influenza C virus were carried out. No recombination signal was found. With the previous evidence in influenza A and B viruses, it seems that homologous recombination has minimal or no effect on influenza virus evolution.